Guarding the Borders of Japan: Occupation, Korean War and Frontier Controls - Tessa Morris-Suzuki (Japan Focus, 2011)
Around 10pm on 5 October 1948 a small boat made its way along the coastline of Cape Sada Peninsula, the long finger of land that juts west from Ehime Prefecture on the Japanese island of Shikoku. The darkness was intense. It was a moonless autumn night, and the forested spine of hills above the jagged cliffs of the peninsula was devoid of lights.The boat – a 20-ton wooden vessel called the Hatsushima1 – had left the heavy swell of the open ocean and now moved slowly and quietly through the calmer waters of the Uwa Sea. No doubt the captain believed that his craft’s progress along this remote stretch of Shikoku coastline was unobserved. In the little fishing villages which dotted its rocky inlets the working day began and ended early, and most of the villagers were already asleep. But from the hills above, eyes were watching.The people of Cape Sada Peninsula in October 1948 were still gradually recovering from the devastation of war. In the last months of the Pacific War the center of the nearest big city, Matsuyama, had been reduced to a burnt-out wasteland by allied fire-bombing.2 The villages had been spared the worst of the air-raids, but during the final stages of the war their fishing boats had been requisitioned by the military or lain idle, unable to venture out into the dangerous waters of war. Men who had been recruited to fight in China or Southeast Asia, and families who had migrated to Manchuria to help build Japan’s Greater East Asia Prosperity Sphere, were still trickling home, transformed by experiences which could seldom be put into words. Many would never return; many remained unaccounted for.